2019
DOI: 10.1371/journal.pone.0215544
|View full text |Cite
|
Sign up to set email alerts
|

A breath of fresh air: Validity and reliability of a Portuguese version of the Multidimensional Dyspnea Profile for patients with COPD

Abstract: Aim To provide a Portuguese version of the Multidimensional Dyspnea Profile (MDP), investigating its validity and reliability in Brazilian patients with COPD. Methods This was a cross-sectional study for translation and linguist validation of the Portuguese MDP version for patients with COPD. The process occurred according to the protocol of Mapi Research Trust, Lyon, France. Three scores of MDP were used for the analysis: the immediate unpleasantness of dyspnea (A1); t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
19
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 13 publications
9
19
2
Order By: Relevance
“…However, the test-retest reliability decreased moderate-to-high after a one-week period. High test-retest reliability results for a short interval (hours to days) have been reported in the other validation studies [5,11,15,16]. Similar to our findings, test-retest reliability tends to decrease after weeks [5,11,16].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…However, the test-retest reliability decreased moderate-to-high after a one-week period. High test-retest reliability results for a short interval (hours to days) have been reported in the other validation studies [5,11,15,16]. Similar to our findings, test-retest reliability tends to decrease after weeks [5,11,16].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the MDP showed a two-factor structure for both determined situations (i.e., activity and rest) similar to findings in the previous validation studies [5,11,15,16,18]. In the original development study of the MDP, three domains were proposed as immediate sensory response, immediate unpleasantness, and resultant emotional response under sensory and affective dimensions based on a well-developed conceptual model of pain perception [3].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations